Gabon : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues on Gabon seeks to quantify the impact of governance reforms on growth. It uses a dynamic stochastic general equilibrium (DSGE) model calibrated to Gabon to simulate the potential benefits from governance and anti-corruption reforms to growth and public debt. Vulnerabilities in the fiscal institutional framework constrain effective revenue collection and reduce the efficiency of public spending, thus limiting fiscal space for priority pro-growth spending. The results of a DSGE model for Gabon suggest that macro-fiscal gains from governance reforms could be substantial. The potential additional growth can range from 0.8 to 1.5 percent per year over the next 10 years, and debt can decline by 1.0 to 2.0 percent of non-oil gross domestic product per year over the same period. It is urgent to improve governance and curb corruption to boost domestic revenue, enhance public finance management and the quality of spending, and improve the business environment to promote private investment and facilitate private sector activity.